1992
DOI: 10.1083/jcb.118.4.961
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of amphiglycan, a novel integral membrane heparan sulfate proteoglycan expressed by epithelial and fibroblastic cells.

Abstract: Abstract. We have synthesized an antisense oligonucleotide primer that matches a supposedly conserved sequence in messages for heparan sulfate proteoglycans with transmembrane orientations. With the aid of this primer we have amplified partial and selected fulllength copies of a message from human lung fibroblasts that codes for a novel integral membrane heparan sulfate proteoglycan. The encoded protein is 198 aminoacids long, with discrete cytoplasmic, transmembrane, and amino-terminal extracellular domains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(75 citation statements)
references
References 45 publications
7
64
0
3
Order By: Relevance
“…Among the cell lines analysed, we found that it was strongly expressed in the ME-180 cells and, to a signi®cantly lesser extent, in HeLa and MCF7 cells, whereas there is almost no expression in Chang, Hec-1B and HEp-2 cells. Expression of syndecan-2 (< 48 kDa in monomeric form and < 80 kDa in dimeric form) has been observed mainly in ®broblasts and endothelial cells (David et al, 1992b). Our results indicate that it is also strongly expressed in Chang and Hec-1B cells and, to a lesser extent, in MCF7 cells.…”
Section: Resultssupporting
confidence: 48%
“…Among the cell lines analysed, we found that it was strongly expressed in the ME-180 cells and, to a signi®cantly lesser extent, in HeLa and MCF7 cells, whereas there is almost no expression in Chang, Hec-1B and HEp-2 cells. Expression of syndecan-2 (< 48 kDa in monomeric form and < 80 kDa in dimeric form) has been observed mainly in ®broblasts and endothelial cells (David et al, 1992b). Our results indicate that it is also strongly expressed in Chang and Hec-1B cells and, to a lesser extent, in MCF7 cells.…”
Section: Resultssupporting
confidence: 48%
“…Neutrophils, normal dermal fibroblasts, and RASFs were generated as described previously (33)(34)(35). Lung fibroblasts were kindly provided by P. Marynen (University of Leuven, Leuven, Belgium [36]), and the normal SFs and normal cervical fibroblasts were provided by E. Van de Leur (RWTH Aachen University Hospital, Aachen, Germany [37,38]). Primary human monocytes were isolated from fresh blood using the Dynal Monocyte Negative Isolation Kit as described by the manufacturer (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…23). We then expressed either PTPσ wild-type (WT) or PTPσ-AAAA in HEK293T cells, treated the cells with heparinase III (hep III; 1 U/mL) for 2 h to remove the HS chains from PTPσ, and stained the cells with a monoclonal 3G10 antibody that reacts only with hep III-treated HS chains (25). We found that cells expressing PTPσ WT, but not PTPσ-AAAA, reacted to the 3G10 antibody (Fig.…”
mentioning
confidence: 97%